2015
DOI: 10.5433/1679-0359.2015v36n6p4031
|View full text |Cite
|
Sign up to set email alerts
|

Sentiency, bioethics and animal welfare: concepts that need to be discussed in higher education to change the teaching and researching paradigm

Abstract: This study investigated the knowledge of students of Veterinary Medicine and Biological Sciences of the State University of Northern Paraná, Campus Luiz Meneghel, on the ethical and legal guidelines of animal experimentation, as well as the possibility of substitute methods for using sentient animals in classes and scientific practices. The research involved 162 freshman students and graduating students, aged 17 to 32 years. The students responded to the questionnaire containing objective and subjective questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…A study with thirteen veterinary schools across several continents found that only one school in Brazil taught an animal welfare course (Federal University of Paraná), while six schools did not (Hewson et al, 2005). Consistent with Duzanski et al (2015) study, most participants in the present study rated teaching animal welfare and bioethics as essential and necessary for professional practice (Tables 2 and 4). In addition, all participants stated that animal welfare should be a required course, thus indicating that veterinarians are receptive to teaching this subject and that higher education institutions should provide these courses systematically.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A study with thirteen veterinary schools across several continents found that only one school in Brazil taught an animal welfare course (Federal University of Paraná), while six schools did not (Hewson et al, 2005). Consistent with Duzanski et al (2015) study, most participants in the present study rated teaching animal welfare and bioethics as essential and necessary for professional practice (Tables 2 and 4). In addition, all participants stated that animal welfare should be a required course, thus indicating that veterinarians are receptive to teaching this subject and that higher education institutions should provide these courses systematically.…”
Section: Discussionsupporting
confidence: 83%
“…Although most participants in the present study (58.3%) stated they had been taught some bioethical ideas, a significant proportion (41.7%) had not. A study conducted with veterinary medicine and biological science students in Paraná found that only 24.7% of participants reported having been taught bioethics before graduation, but all of them rated it significant (Duzanski et al, 2015). In the present study, most participants from Rio de Janeiro and Paraná reported that their schools taught bioethics as an autonomous discipline.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation